In vivo anti-ulceration effect of Pancratium maritimum extract against ethanol-induced rats via NLRP3 inflammasome and HMGB1/TLR4/MYD88/NF-κβ signaling pathways and its extract metabolite profile - Rehab F. Taher; Eman M. Abd El ghany; Zeinab A. El-Gendy; Mai M. Elghonemy; Heba A. Hassan; Gehad A. Abdel Jaleel; Azza Hassan; Tushar C. Sarker; Ahmed M. Abd-ElGawad; Mohamed A. Farag; Abdelsamed I. Elshamy (PLoS ONE, 2025)
Background Gastric ulcer is a multifaceted ailment of multiple causes and is chronic warranting the discovery of remedies to alleviate its symptoms and severity. Pancratium maritimum L. is recognized for its several health benefits, although its potential against gastric ulcers has yet to be reported. Methods and findings This study reports on the effects of P. maritimum L. whole plant (PM-EtOH) ethanol extract at a dose of 25, 50, and 100 mg/kg body weight orally for managing ethanol-induced peptic ulcer in rats. The anti-ulceration capacity of PM-EtOH was determined against ethanol (EtOH)-induced rats via biochemical, histological, immunohistochemical, and western blotting assays. The profiling of the bioactive metabolites in P. maritimum extract was based on Ultra-high-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (UHPLC-ESI-qTOF-MS/MS) analysis. Following PM-EtOH treated group, the gastric glutathione (GSH) level dropped in the ulcer group receiving ethanol was restored to normal levels. Additionally, following PM-EtOH, elevated malondialdehyde (MDA) content in the stomach tissues diminished. PM-EtOH treated group displayed recovery and comparable morphology compared with normal group, concurrent with lower levels of Tumor Necrosis Factor α (TNF-α), MyD88, and NLRP3, along with low expression of Nuclear Factor kappa β (NF-кβ) and high-mobility group box protein 1 (HMGB1) proteins. Immune-histochemicals of caspase-3 and toll-like receptors-4 (TLR-4) showed their normalization. These findings imply that PM-EtOH exerts a protective effect on rat stomach damage that has yet to be further tested in clinical trials for treatment of stomach ulcers. Phytochemical profiling of PM-EtOH via UHPLC-ESI-qTOF-MS/MS led to the identification of 84 metabolites belonging to amino acids, organic acids, phenolic acids, alkaloids, flavonoids, and fatty acids to likely mediate for the observed effects. Conclusions These outcomes provided evidence for the potential of PM-EtOH in gastric ulcers management.